Comparison of Effectiveness of Hydropobic Cutimed Sorbact Versus Cadexomer Iodine 0.9% on Healing of Diabetic Foot Ulcer: A Randomized Control Trial - Septian Mixrova Sebayang; Asmat Burhan (Indonesian Science Media, 2024)
Background: Diabetic foot ulcers have risen with DM. The IDF reports 15-25% of diabetics get foot ulcers, rising to 25% over time. Due to biofilm and bacteria growth, diabetic ulcers need advanced wound therapy using antimicrobial dressings. Modern antibacterial treatments include sorbact hydrophobic and 0.9% cadexomer iodine. Purpose: Analyse the effectiveness of cutimed sorbact hydrophobic with cadexomer iodine 0.9% on diabetic ulcer infection. Methods: A single-blind, fold-over, randomised controlled study. Patients with diabetes who developed foot ulcers between September 1 and December 1, 2023. One hundred sixty-two participants were randomly assigned to receive cutimed sorbact hydrophobic or cadexomer iodine 0.9%. After 120 days, both groups. Results: It was found that the two groups had similar body mass index (0.364), wound size (0.317), and baseline age (p=0.432). The mean difference in confidence value of -0.16 (OR -2.54 to 1.29; p=0.058) showed that diabetic foot ulcers in both groups had similar wound size on the thirtyth day. On day 60 of treatment, Sorbact Hydropobic showed a difference of 22.56±9.87 compared to Cadexomer Iodine 0.9%, with an MD-CI value of -6.75 (OR 5.19 to -0.34; p=0.039 At 90 days of treatment, cadexomer iodine showed a significant difference from sorbact hydropobic (9.73±2.14), with an MD-CI value of -12.29 (OR -9.19 to -4.26; p=0.016; R2=-0.417). Conclusion: Sorbact Hydropobic reduces wound size, infection, and bacterial resistance, speeding chronic wound healing. On chronic wounds, hydropobic sorbact can be used as a primary dressing.